A Comprehensive Systematic Review of The Relationship Between Onset-to-Needle Time and Recanalization Success in Ischemic Stroke - Rosi Rahmadarti; Dino Adijaya (The International Journal of Medical Science and Health Research, 2026)
Introduction: The effectiveness of reperfusion therapies in acute ischemic stroke is highly time-dependent, with earlier treatment generally associated with better outcomes. However, the precise relationship between onset-to-needle time (ONT) and recanalization success, and how this relationship varies across treatment modalities and patient subgroups, requires systematic synthesis of the extensive and sometimes heterogeneous evidence. Methods: A systematic review was conducted, screening sources based on strict criteria including adult acute ischemic stroke patients receiving intravenous thrombolysis (IVT), clear reporting of ONT, and assessment of recanalization via validated imaging. Data were extracted from 80 eligible studies, encompassing randomized controlled trials, cohort studies, and meta-analyses, with sample sizes ranging from 24 to 12,529 patients. Extraction focused on time metrics, treatment modalities, recanalization rates, functional outcomes, safety data, and statistical relationships. Results: A strong inverse relationship exists between ONT and recanalization success. Ultra-early treatment within the "golden hour" (≤60 minutes) achieved a 44% recanalization rate compared to 12% when treated after one hour (Bernatowicz et al., 2016). A clear dose-response effect was evident, with the odds of favorable outcome declining from 2.8 for treatment within 90 minutes to 1.2 for 271-360 minutes (Hacke et al., 2004). For patients with large vessel occlusion (LVO) receiving bridging IVT before thrombectomy, the benefit becomes non-significant beyond approximately 2 hours 20 minutes (Kaesmacher et al., 2024). Each 15-minute delay in door-to-needle time was associated with 20.3 fewer excellent outcomes per 1000 patients (Goyal et al., 2019). Safety outcomes, including symptomatic intracranial hemorrhage rates, did not show a significant increase with earlier treatment. Discussion: The synthesized evidence underscores "time is brain" as a fundamental principle. Heterogeneity in effect sizes is explained by differences in patient populations (e.g., LVO vs. non-LVO), treatment contexts (IVT alone vs. bridging therapy), and study methodologies. The benefit of IVT extends to extended time windows (4.5-24 hours) when guided by advanced imaging selection (Campbell et al., 2020; Rahmati et al., 2025). Workflow innovations, such as mobile stroke units and protocols favoring tenecteplase, significantly reduce critical time intervals and improve outcomes (Czap et al., 2021; Henderson et al., 2024). Conclusion: Earlier onset-to-needle time is consistently and powerfully associated with higher rates of successful recanalization and improved functional independence in acute ischemic stroke. This relationship is quantifiable and should drive clinical protocols and public health initiatives aimed at minimizing all pre- and in-hospital delays. Treatment decisions in extended windows must be individualized using advanced neuroimaging.